2006
DOI: 10.1177/0145445504272977
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Outcome in Parent-Child Interaction Therapy

Abstract: This study explored predictors of treatment response and attrition in Parent-Child Interaction Therapy (PCIT). Participants were 99 families of 3- to 6-year-old children with disruptive behavior disorders. Multiple logistic regression was used to identify those pretreatment child, family, and accessibility factors that were predictive of success or attrition. For all study participants, waitlist group assignment and maternal age were the significant predictors of outcome. For treatment participants (study part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
104
6
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 52 publications
21
104
6
2
Order By: Relevance
“…Many researchers studying this phenomenon use samples of children 7 with widely variable clinical problems, which is problematic because different variables may predict premature termination among children with different diagnoses (Kazdin & Mazurick, 1994;Kazdin 1996). A number of researchers have tried to remedy this problem by studying premature termination in relatively homogeneous samples of children participating in universitybased, randomized-control trials (Kazdin & Mazurick, 1994;Kendall & Sugarman, 1997;Werba, Eyberg, Boggs & Algina, 2006). However, results from these studies may not generalize to children receiving treatments within community settings .…”
Section: Problems With the Existing Literature On Children's Engagemementioning
confidence: 99%
“…Many researchers studying this phenomenon use samples of children 7 with widely variable clinical problems, which is problematic because different variables may predict premature termination among children with different diagnoses (Kazdin & Mazurick, 1994;Kazdin 1996). A number of researchers have tried to remedy this problem by studying premature termination in relatively homogeneous samples of children participating in universitybased, randomized-control trials (Kazdin & Mazurick, 1994;Kendall & Sugarman, 1997;Werba, Eyberg, Boggs & Algina, 2006). However, results from these studies may not generalize to children receiving treatments within community settings .…”
Section: Problems With the Existing Literature On Children's Engagemementioning
confidence: 99%
“…One study showed that older mothers were more likely to attend the treatment and not to drop out of the study [59]. On the other hand, children of younger mothers sometimes had better outcomes [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, they demonstrated high intervention completion rates (71%) consistent with, and in some cases higher than, other PCIT studies (e.g., Antonini et al, 2012;Boggs et al, 2005;Schuhmann et al, 1998;Werba & Eyberg, 2006). Moreover, completion rates for the current study fare well relative to other evidenced-based parent training programs with attrition rates approaching 50% (Reyno & McGrath, 2006), and family-focused TBI interventions with attrition rates between 56% and 76% (Antonini et al, 2014(Antonini et al, , 2012.…”
Section: Summary Of the Current Worksupporting
confidence: 80%
“…Notably, caregivers who dropped out of the intervention endorsed multiple psychosocial stressors during the time they were enrolled in the study, which may have contributed to their inability to complete the intervention. Nonetheless, the fact that the retention rate for the current intervention, which was delivered twice per week, was similar and in some cases better than previously documented rates for weekly inperson and web-based interventions (Antonini et al, 2012;Boggs et al, 2005;Schuhmann et al, 1998;Werba et al, 2006), provides preliminary evidence regarding the feasibility of this time-limited and intensive approach to intervention. Notably, two families relied primarily on public and medical transportation during the study and still completed the intervention in spite of significant transportation barriers.…”
Section: Summary Of the Current Worksupporting
confidence: 55%